THE RELATIONSHIP OF PREGNANCY EXERCISE TO PERINEAL RUPTURE AMONG PRIMIPAROUS WOMEN AT PMB DINCE SAFRINA OF PEKANBARU IN 2015 -2018 - Hardyanti, ining; Harahap, Juraida Roito; Laila, Ani (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2020)
AbstractPerineal rupture is one of the complications that occurs during labor that can lead to death in the mother. The impact of perineal rupture is bleeding duringthe first hour after childbirth, fistulae, hematoma, and infection. One of thepreventive efforts that can be done to reduce perineal rupture is pregnancyexercises. The results of a preliminary survey conducted at PMB Dince Safrinashowed that 66.1% out of 186 women giving birth experienced perinealrupture. This study aimed to determine the relationship between pregnancyexercise and perineal rupture in primiparous women in PMB Dince Safrina in2015-2018. This quantitative research method used a cross sectional design.The population was all primiparous mothers at PMB Dince Safrina in 2015up to 2018 with 219 people. The sampling technique used was totalsampling. The data analysis used univariate and bivariate with the chi-squarestatistical test. The results showed that 55.25% of primiparous mothers didpregnancy exercise and 58.40% experienced perineal rupture. The results ofstatistical tests obtained a p-value of 0.000, meaning there was a significantrelationship between pregnancy exercise and the incidence of perinealrupture in primiparous women with OR of 0.239, indicating that those whodid not do pregnancy exercise would experience perineal rupture 0.239times than those who did. It is suggested to midwives to maintain pregnancyexercise classes and provide health education to pregnant women to be moreactive in carrying out pregnancy exercises to prevent the occurrence ofperineal rupture during labor.